2013
DOI: 10.4103/2230-8210.111672
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diagnosis of multiple endocrine neoplasia-1 unraveled during workup of virilization caused by adrenocortical carcinoma

Abstract: Multiple endocrine neoplasia-1 (MEN1) is an autosomal dominant syndrome with classic triad of parathyroid hyperplasia, pancreatic neuroendocrine tumors, and pituitary adenomas. Other recognized manifestations include carcinoid, cutaneous or adrenocortical tumors. It is commonly presented with clinical features related to parathyroid, pancreas or pituitary lesions. Here, we have presented a case that had virilization and biochemical Cushing's syndrome due to adrenocortical carcinoma as presenting feature of MEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…By a thorough literature review, we found additional 19 cases of ACC associated with MEN1 from nine reports (Supplementary Table 2) (1, 2, 3, 4, 5, 6, 7, 8, 9). None of the 19 cases were related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By a thorough literature review, we found additional 19 cases of ACC associated with MEN1 from nine reports (Supplementary Table 2) (1, 2, 3, 4, 5, 6, 7, 8, 9). None of the 19 cases were related.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal lesions occur in 20–55% of MEN1 cases and the majority is adrenocortical adenomas or hyperplasia. A small fraction of MEN1 patients developed adrenocortical carcinoma (ACC) (1, 2, 3, 4, 5, 6, 7, 8, 9). In fact, ACC in general is a rare malignancy with high mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenocortical carcinoma can exhibit familial aggregation in MEN1 patients. In reviewing literature, we could document 22 cases of adrenocortical carcinoma associated with MEN1 (5,63,65,(97)(98)(99)(100)(101)(102)(103)(104)(105). The most peculiar and aggressive MEN1 phenotypes associated with adrenocortical carcinoma were recently described (104,105).…”
Section: Adrenocortical Carcinomamentioning
confidence: 99%
“…The tumor cells also expressed immunoreactivity to cytokeratin and vimentin, and Ki67 index was approximately 2%. Multiple endocrine neoplasia 1 is an autosomal dominant endocrine syndrome with classic triad of parathyroid hyperplasia, pancreatic neuroendocrine tumors, and pituitary adenomas 1,2 . Adrenocortical carcinomas are rarely associated with MEN1 syndrome 3,4 .…”
mentioning
confidence: 99%
“…Multiple endocrine neoplasia 1 is an autosomal dominant endocrine syndrome with classic triad of parathyroid hyperplasia, pancreatic neuroendocrine tumors, and pituitary adenomas. 1,2 Adrenocortical carcinomas are rarely associated with MEN1 syndrome. 3,4 In 60% to 85% of adults with adrenocortical carcinoma, patients present with a large mass or symptoms related to mass effect.…”
mentioning
confidence: 99%